ANALISIS KEPUASAN PELANGGAN CHI-CHI’S MEXICAN RESTAURANT PADA PT. BERKAH MANCA BOGA (KODEL GROUP) JAKARTA - RINOVIAN RAIS (SMART Management Journal, 2021)
The major problem in this research is the low customer satisfaction awareness at Chi-Chi‟s Mexican Restaurant under PT. Berkah Manca Boga, Jakarta. This low awareness caused by the top management has not paid full attention to this problem. The customer services qualities become a major focus to all organizations in all industries nowadays. This focus is caused by tight competition, technology development and economy growth. In the competitive side, services and customer satisfaction become the strength offered by each company due to many competitors offering similar products. Technology development also gives more opportunities for product and services innovation at the same time. Customers nowadays are also becoming more demanding and have more bargaining power to the companies. Moreover, people nowadays are in the evolution stage to become the knowledge economy society, giving insight that customer satisfaction becomes one the tools to gain success